(untitled) (Nepal Medical College Journal, 2021)
Thoracentesis is tapping of pleural fluid from the pleural cavity for either diagnostic or therapeutic purposes. These are the frequently encountered procedures in the medical practices. Many conditions warrant sending the cases of pleural effusion cases for intervention. Most of the cases had been tried blindly first in their respective departments but failed because of various reasons. It had been documented regarding the advantages and disadvantages of blind and ultrasonography (USG) guided procedures. The aim of the study was to highlight the advantages and benefits of USG guided thoracentesis. We carried out USG guided thoracentesis of fifty cases in our radiology section who were referred to us by various departments. There were 19 female (38%) and 31 male (62%) patients. All these candidates had failed in blind procedures, when tried first. All these cases underwent USG guided thoracentesis with almost negligible complications. These were found to be having pleural fluid collection due to different underlying pathologies. There was no major complication in any of the cases who underwent thoracentesis. We reiterate by this study that USG guided procedures in thoracentesis should be the first choice in the tapping of pleural fluid. This is a quick, affordable, and without any discomfort to the patient.